Evidentiary Value of Internet Protocol Address Similarity in Tender Collusion: a Study of Case No. 445 K/PDT.SUS-KPPU/2021 - Raissa Sundari; Rismawati Rismawati (Fox Justi : Jurnal Ilmu Hukum, 2026)
Background: Collusion in electronic tenders represents a fundamental violation of fair competition principles, as it systematically undermines the transparency, fairness, and efficiency of government procurement processes, prompting the adoption of the e-tender system to safeguard integrity. Objectives: This study aims to critically assess the legal validity and probative strength of IP addresses as electronic evidence in digital collusion cases, while specifically examining the judicial reasoning applied in relevant Indonesian court decisions. Methods: Employing a normative legal methodology with a descriptive-analytical approach, this research draws upon diverse legal literature, statutes, and comparative case studies. Results: The analysis establishes that while Article 5 of Indonesia's ITE Law formally recognizes IP addresses as valid electronic evidence due to their unique device-identifying function, the ruling in Decision Number 445 K/Pdt.Sus-KPPU/2021 is jurisprudentially flawed; the court erroneously limited the comparison of IP addresses to a superficial administrative verification by the procurement working group (pokja), despite the pokja lacking statutory access to the SPSE system. In contrast, international jurisdictions such as Brazil, Singapore, and China robustly admit IP addresses as compelling evidence when corroborated by metadata and system logs. Conclusions: Consequently, this study underscores the urgent necessity for Indonesia to establish consistent, technology-adaptive, and procedurally clear standards for electronic evidence to ensure legal certainty and reinforce the effective enforcement of fair competition law in the digital procurement landscape.